Beneficial effects of Chinese herbs in the treatment of fatty liver diseases - Panyod, Suraphan; Sheen, Lee-Yan (Journal of Traditional and Complementary Medicine, 2020)
Eating habits and lifestyle directly impact general health. Consumption of fat- and sugar-rich foods and alcohol increase the risk of developing fatty liver disease. The prevalence of fatty liver disease is markedly critical, and its pathogenesis and progression are complicated. Chinese herbal medicine has been used to treat and prevent human diseases through-out history, and is a rich source of biologically active substances with unique curative properties. More recently, Chinese herbs and their extracts have been identified as a novel source of potential therapeutic agents in the prevention and treatment of fatty liver disease. Beneficial effects of these herbal medicines mean that they can be classified as novel candidates for the treatment and prevention of both alcoholic fatty liver disease (AFLD) and non-alcoholic fatty liver disease (NAFLD), in place of conventional allopathic treatments. In this review, we explore the current literature related to herbal medicines used for the treatment of or protection against fatty liver diseases and describe their mechanisms of action.